IRF7-deficient MDBK cell based on CRISPR/Cas9 technology for enhancing IBRV replication - Ge, Guiyang; Li, Dongli; Ling, Qian; Xu, Lihui; Ata, Emad Beshir; Wang, Xiaolin; Li, Keyan; Hao, Wen; Gong, Qinglong; Li, Jianming; Shi, Kun; Leng, Xue; et al. (Frontiers in Microbiology, 2024)
Infectious bovine rhinotracheitis (IBR), characterized by acute respiratory lesions in cattle, is a major infectious disease caused by bovine alphaherpesvirus-1 (BoAHV-1). Control of this disease is primarily depending on vaccination. Madin-Darby bovine kidney cells (MDBK) being the main host cells and the important production platform for IBR vaccines. However, innate immune genes inhibit viral replication. Accordingly, the aim of this study was developing of IRF7 gene deleted MDBK cells to facilitate the production of high-titer vaccines. The CRISPR/Cas9 technology was used to knock out the IRF7 gene in MDBK cells and the impact on virus replication was examined using virus growth curves, CCK-8 assays, cell scratch assays, and qPCR. The knockout of the IRF7 gene in MDBK cells led to an increased replication capacity of IBRV and a significant reduction in type I interferons expression, specifically IFN-α and IFN-β. This indicates that IRF7−/−MDBK cell lines can effectively result in production of IBRV with high-titer, which will enhance the development of inactivated or attenuated vaccines.